Challenges before the reservation discourse - Palshikar, Suhas (2008)
The Supreme Court judgment does not mean the end of the debate on reservations. A long-standing challenge for those who support affirmative action is to end the phenomenon of quotas being an instrument of political mobilisation rather than a mechanism to ensure social justice. the main issues that need addressing are identification of Other Backward Classes, the criteria for deciding the creamy layer and the fallout of sub-classification of the intended beneficiaries. None of these issues can be seen as having been permanently decided by the Mondal Commission or the courts nor can they be seen as not changing over time. - Reproduced.
Keywords: Backward classes